Growing Apart: How Italy’s Populist Radical Right Electorates Diverged in the 2024 EP Election - Mirko Crulli; Mattia Gatti (Italian Political Science)
A further swing to the right characterised the 2024 European Parliament (EP) election. The Populist Radical Right (PRR) gained ground, becoming the most voted alternative in six European countries. Among these is Italy, where the honeymoon between Giorgia Meloni’s Fratelli d’Italia (FdI) and its electorate persisted after 20 months of a fully right-wing cabinet comprising another PRR party, the Lega. Leveraging on an original survey conducted by the Italian Centre for Electoral Studies (CISE), we explore the determinants of PRR voting in the 2024 EP election in Italy. We test two classical theories of PRR voting: ‘cultural backlash’ and ‘economic insecurity’. We also assess whether perceived local decline, recently identified as an important predictor of PRR orientations, played a role even in the EP election, an arena where local concerns should count less. Finally, we look at the impact of European issues and the major crises of the early 2020s, notably the Covid-19 pandemic, the Russia-Ukraine war, and the Israel-Hamas conflict. The takeaway is that the FdI and Lega electorates have grown apart: while still sharing nativism – a core ideological feature of the PRR family – they differ in other relevant aspects, notably socio-economic class and EU-related positions. The implications of these findings for the broader debate on the demand for PRR politics are discussed in the conclusion.